Labeling of pickled vegetable products produced by agroindustries: compliance analysis based on the Brazilian legislation - LOZER, Priscila Endlich; ROSÁRIO, Denes Kaic Alves; SÃO JOSÉ, Jackline Freitas Brilhante de (Food Science and Technology, 2023)
Labeling is an important tool used to provide consumers with information about food products in compliance with health regulations. The aim of this study was to investigate the compliance of labels associated with pickled vegetable products produced by rural family agroindustries in the Serrana Region, Espírito Santo State, Brazil, with the Brazilian sanitary surveillance legislation. Secondary data from the State Food Monitoring Program developed by Espírito Santo State’s sanitary surveillance agency were herein used. Collected data were systematized into a legislation-based checklist comprising 108 items that were divided into 8 blocks, namely, General principles, Language, Mandatory information, Mandatory information presentation and distribution, Voluntary labeling, Gluten, Allergens, and Nutritional labeling of packaged foods. The results were analyzed through descriptive statistics, multivariate data analysis based on the Ward method, and non-hierarchical data analysis based on the K-means method. The minimum and maximum adequacy rates reached 23.1% and 94.3%, respectively, and the mean adequacy rate was 57.1%. The highest non-compliance mean values were linked to nutritional labeling (66.4%), gluten-incidence indication (55.2%), voluntary labeling (56.0%), and mandatory information presentation and distribution (42.8%). All product labels were classified as non-compliant; therefore, the health legislation was not met.